Predictors of Perceived Need for and Actual Action Taking Among Women in Violent Relationships. Issue 16 (August 2019) - Katerndahl, David A.; Burge, Sandra K.; Ferrer, Robert L.; Becho, Johanna; Wood, Robert
Decision-making of women in violent relationships is poorly understood. The study seeks to identify predictors of need-for-action and actions taken by women in violent relationships. The participants were 143 women who experienced violence in previous month from 6 primary care clinics. The methods involved multiple times series using daily assessments of household environment, marital relationship, concerns, violence, and need-for-action collected via telephone interactive voice response for 8 weeks. Outcomes include daily need-for-action and reports of actions taken. Same-day correlates and prior-day associations using vector autoregressions were sought, combined across subjects using meta-analytic techniques. Need for help depended on stalking, concern for child safety, forgiveness, and low perceived control; actually seeking help depended on sense of control with same-day stress and need for help. Need for legal action depended on concern for child safety and finances with desire to keep family together; actually taking legal action, correlated only with prior-day stalking and concerns about child safety but less about effects of violence on child. Need to leave depended on his violence, with concern about its effect on child, her forgiveness, and a low desire to keep family together, while actually leaving was primed by a day of his drinking, and triggered by same-day stress and need to leave, but lower levels of her drinking or his seeking forgiveness. Once gone, prior-day stalking and his alcohol use correlated with returning to the relationship. Taking action depends upon few prior- and same-day factors unique to each action.